Cursos de derecho international (O.A.S. Subsecretariat de Asuntos Juridicos WashingtonUS, 2002)
Deals with various aspects of international law as well as with conflict of laws. Focuses on Latin America
Contents: v.1. pts. 1&2 El Derecho international privado en las Americas (1974-2000). - v. 2. pts. 1&2 El Sistems internericano (1974-2001)